Long-term effects of an alcohol prevention program at licensed premises: a Swedish 20-year follow-up study - Elgán, Tobias H.; Andréasson, Sven; Gripenberg, Johanna (Frontiers in Public Health, 2024)
In 1996, a multicomponent community-based alcohol prevention program in Responsible Beverage Service (RBS) targeting licensed premises was developed by STAD (Stockholm Prevents Alcohol and Drug Problems) and implemented in Stockholm, Sweden. The program consists of community mobilization and collaboration, training, and enforcement. Early evaluations have shown a significant increase in the refusal rates of alcohol service to intoxicated patrons, from 5% in 1996 to 70% in 2001, and a 29% decrease in the frequency of police-reported violence. A cost-effectiveness analysis showed a costsaving ratio of 1:39. The program was institutionalized by a collaborative steering group consisting of community stakeholders. This study aimed to evaluate the long-term effects over 20 years of the RBS program. The indicator chosen was the rate of alcohol overserving to obviously intoxicated patrons at licensed premises in Stockholm. Methods: A 20-year follow-up study was conducted using the same procedure as the baseline and previous followups. Professional male actors (pseudopatrons) were trained by an expert panel to enact a standardized scene of obvious alcohol-intoxication. In 2016, 146 licensed premises located in the central part of Stockholm were randomly selected and visited. A review of program implementation from its initiation 1996 was conducted, examining critical events, including commitment from key actors in the community, training of bar staff, and enforcement. Results: At the 20-year follow-up, pseudopatrons were refused alcohol service in 76.7% of the attempts, which was at the same level (70%) as in the follow-up in 2001, thus indicating sustained effects of the RBS program. Compared with previous follow-ups, serving staff used * A research and development unit within STAD responsible for the initiation and coordination of the intervention.